Prevalencia de vacas gestantes en el matadero municipal de la parroquia portoviejo. - Vélez Alcívar, Alexi Leonardo (2016)
This research was conducted in the Municipal Slaughterhouse of Portoviejo Parish in order to assess the prevalence of pregnant females postmortem, 837 bovines of different ages and weights were slaughtered. Cows were carried evisceration room where the gestation period was determined by the technique of observation. Data were analyzed using descriptive statistics. greater number of cattle slaughter in females, 711 cows representing 84.95% were males and 126 corresponding to 15.05% was recorded. 195 cows were slaughtered in a state of pregnancy, which were classified in stages according to the time of gestation, after measuring the occipito-sacral length in cm of fetuses with a tape measure the following values were found in days of embryonic and fetal pregnancy : 7 to 45 equivalent to 7.18%, representing 46-90 29.74%, 91 to 180% constitutes and 42.56 181-270 20.52% meaning. Regarding the sex of fetuses; he obtained the highest number with 108 female fetuses corresponding to 55.38%, males were 73 concerns the 37.44% and 14 embryos is equivalent to 7.18% that can not be identified macroscopically sex were found . The economic interpretation of this paper concludes that for every cow slaughtered pregnant breeding lost $ 516,00 US dollars, of which corresponds loss in milk production $ 336.00, and for loss of unborn babies to $ 180.00.